Recurrent collaural fistula: a challenge - Pol, Shashikant Anil; Singhal, Surinder K.; Gupta, Nitin; Sivanandan, Shalima Pulpra (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Collaural fistula or cervico-aural fistula is a rare anomaly accounting for less than 8% of first branchial cleft anomaly. Aberrant development of first branchial cleft may lead to formation of a cervical cyst or sinus in the region of ear. We reported a case of a 4 year old girl who presented with recurrent swelling in right infra-auricular region from 6 months of age. She had undergone incision and drainage of the swelling three times at various peripheral hospitals over past 3.5 years. On examination two sinuses were noticed surrounding lobule of right pinna of which one was present posterior to the lobule and second was present just above lobule at lateral most part of conchal cartilage. Diagnosis of recurrent infected collaural fistula requires detailed clinical examination for presence of multiple sinuses surrounding the lobule and external auditory canal. In case of non visibility of sinus in external auditory canal, microscopic examination should be done. CT sonogram and MRI are useful diagnostic tools for recurrent infected fistulas. Surgical excision of whole tract is the definitive treatment but superficial parotidectomy along with it can reduce chances of recurrence significantly. If more than 30% of the circumference of external auditory canal is involved then split skin grafting is required for the coverage. Diagnosis of collaural fistula should be kept in mind whenever there is recurrent postaural or infra-aural swelling mainly in paediatric patients. Superficial parotidectomy along with complete excision reduces the recurrence rate. Facial nerve palsy can be a devastating complication of surgery.